(untitled) (Annals of Medical Research, 2021)
Aim: The aim of the present study was to evaluate the relationship between the results of the 50-g oral glucose tolerance test (OGTT) and macrosomia and large for gestational age (LGA) in non-gestational diabetes mellitus (GDM) pregnant women. Materials and Methods: Our retrospective study comprised 980 pregnant women18–40 years old, within 24–28 weeks of gestation, and having a singleton pregnancy. GDM was screened using the 50-g OGTT. Patients were divided into three groups according to the OGTT results as follows: (1) 1-h plasma glucose levels >140 mg/dL and normal 100-g OGTT results (false-positive group), (2) 1-h plasma glucose levels between 130 and 139mg/dL, and (3) 1-h plasma glucose levels <130mg/dL. Results: Maternal characteristics were similar among the groups. Fetal weight was 3050±410g in the false-positive group, 3150±390g in the 130–139mg/dL group, and 3100±420g in the <130mg/dL group. Fetal weight was statistically similar among the groups (p= 0.910). Macrosomia was determined in 2 patients (1.25%) in the false-positive group, 3 (1.07%) in the 130–139mg/dL group, and 6 (1.1%) in the <130mg/dL group. These rates were statistically similar among the groups (p =0.175). LGA was determined in 21 patients (13.1%) in the false-positive group, 38 (13.5%) in the 130–139mg/dL group, and 70 (12.9%) in the <130mg/dL group. These rates were statistically similar among the groups (p = 0.450). Conclusion: Our results indicated that macrosomia and LGA rates were similar among groups and 50-g OGTT seems to have a low capacity for predicting macrosomia and LGA in pregnant women without GDM.